Strategi Marketing UMKM Perlengkapan Pernikahan (Rona Creation) Di Desa Pacekulon Pada Masa PPKM Darurat Untuk Meningkatkan Target Penjualan - Nila Zaimatus Septiana; Muhammad Reza Firdaus (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2021)
The emergence of the Covid-19 pandemic and the issuance of an emergency PPKM decree resulted in a decline in production and marketing activities for MSME actors. The purpose of this study was to find out how the Marketing Strategy of MSMEs for WeddingEquipment in Pacekulon Village During the Emergency PPKM To Increase Sales Targets. The method used in this research is using qualitative research methods. The subject of this research is MSME Wedding Equipment which is located in Pacekulon village, Nganjuk. Sources of data used in this study using primary data and secondary data. Data collection techniques in this study using interviews. This reasearch data analysis uses qualitative analysis from Miles and Hubberman. The results of this study were to deal with emergency PPKM for MSMEs for Wedding Equipment in Pacekulon village to apply online marketing strategies through social media applications such as WhatsApp, Instagram, and Facebook, although there were decreased orders for some of their products due to the pandemic and emergency PPKM.